Optimization of the alkaline treatment for Agave americana fiber and its influence on the mechanical properties of fly ash-based geopolymer - Rojas Clemente, Shirley Melanie (2021)
Geopolymers are good alternatives for replacing ordinary Portland cement (OPC) due to their comparable properties and feasibility to be obtained from industrial by-products. As OPC, geopolymers have superior compressive strength but a brittle behavior that the addition of fibers can improve. When the first macrocrack appears, fibers develop bridging mechanisms to allow the proper distribution of loads, so the composite can enable multiple cracks and enhance its ductility. At present, a wide range of materials can be used to reinforce cementitious matrices, from synthetics such as steel, glass, carbon, and polypropylene to natural fibers such as cotton, sweet sorghum, oil palm, coir, jute, sisal, flax, bamboo, etc. Natural fibers are among the most accepted resources to reinforce composites because they are biodegradable, renewable and generally, have a less environmental impact than their synthetic counterparts. They have low density and specific mechanical properties comparable to fibers made of glass, making them materials with a good performance-price ratio. However, their high variability of properties and hydrophilic behavior can create issues when reinforcing a matrix. Chemical treatments are used to clean chemical compounds that do not contribute to the fiber strength and favor moisture absorption. After treatment, the fiber surface increases its roughness which enhances the interlocking within the composite. This thesis investigates the mechanical properties of Agave americana fibers obtained by beating and boiling the leaves. The fibers were subjected at 1%, 5%, and 20% NaOH concentrations over 0.5 hr, 1 hr, and 3 hr and tested to determine the tensile strength. The surfaces were also analyzed by scanning electron microscopy (SEM). After treatment, most of the fibers enhanced the tensile strength and strain and 1% NaOH concentration over 1 hr was chosen as the optimum condition. Then, fibers were treated at the optimum condition and added to the geopolymer mixture at different doses: 0.5%, 0.75%, and 1% by weight of fly ash. The geopolymers were tested at compressive, flexural, and splitting tensile loads at 7 days of age. The compressive strength increased by 12% at 0.75 (wt.%) and the modulus of elasticity in compression, 13% at 1% (wt.%). Also, the tensile strength increased by 36% at 1 (wt.%). However, the flexural strength decreased probably due to the fiber length. Still, further studies are needed to understand the influence of the fiber length on the mechanical properties of geopolymers. Finally, the SEM analysis was conducted to identify the fiber failure modes.